Examination of the influence of material and design parameters on the development of cracks due to the action of an elevated groundwater table - Berkowski Piotr; Dmochowski Grzegorz (MATEC Web of Conferences)
One of the solutions to the problem of deep underground foundations in unfavourable soil and water conditions is to build a basement structure in the form of a so-called concrete “white box”. In such a case, protection against groundwater penetration is done by using concrete of an appropriate class and waterproofing level. It is also obvious that in designing a foundation slab with a high level of groundwater special attention should be paid to the correct calculations of the basic reinforcement, because too little of it can lead to the formation of cracks exceeding 0.2 mm, which in turn can periodically result in the formation of deep cracks and significant groundwater leaks inside the underground storey of building. The article presents case study of the process of determining the causes of crack development, which is documented by structural examinations and calculations.